TINGKAT KENYAMANAN HUTAN KOTA BUNGKIRIT DI KABUPATEN KUNINGAN BERDASARKAN KERAPATAN VEGETASI, IKLIM MIKRO DAN PERSEPSI MASYARAKAT - Silvi Sahidah; Iing Nasihin; Deni Deni (Journal of Forestry And Environment, 2022)
Green Open Space is part of the open space of an urban area filled with plant vegetation, one of which is the City Forest. Bungkirit City Forest is part of the green open space in Kuningan Regency which is maintained to overcome environmental problems. The existence of this urban forest is an important component in maintaining the comfort of the city for its residents through the function of forming the city's microclimate. This research aims to identify the types of trees that make up the City Forest, determine comfort based on the Temperature Humidity Index (THI) and community perception. Vegetation data is carried out by vegetation analysis to determine the type and number of trees, composition of vegetation types and tree density, determining data collection points is carried out based on the purposive method. Air temperature and humidity were collected by measuring within 5 weeks using a thermohygrometer, while perception data was collected by interview using a questionnaire. The results of identifying tree vegetation show that there is an influence of vegetation density on air temperature and humidity which influences the level of comfort with the composition of vegetation types dominated by the Gmelina (Gmelina arborea) type. The THI value inside the Bungkirit City Forest area can be categorized as comfortable, seen from the average for 5 weeks, the comfort index reaches 24.25, while outside the area it falls into the uncomfortable category with an average comfort index reaching 26.73, which means the value This exceeds the moderate category level, namely 26. The comfort level of Bungkirit City Forest based on perception is relatively high, with 87.5% stating that it is comfortable.Ruang Terbuka Hijau (RTH) merupakan bagian ruang terbuka dari suatu kawasan perkotaan yang diisi oleh vegetasi tumbuhan, salah satunya yaitu Hutan Kota. Hutan Kota Bungkirit merupakan bagian dari ruang terbuka hijau di Kabupaten Kuningan yang dipertahankan keberadaannya untuk mengatasi permasalahan lingkungan. Keberadaan hutan kota ini merupakan komponen penting dalam mempertahankan kenyamanan kota bagi penduduknya melalui fungsi pembentuk iklim mikro kota. Penelitian ini bertujuan mengidentifikasi jenis pohon penyusun Hutan Kota, mengetahui kenyamanan berdasarkan Temperature Humidity Index (THI) serta persepsi masyarakat. Data vegetasi dilakukan dengan analisis vegetasi untuk mengetahui jenis dan jumlah pohon, komposisi jenis vegetasi dan kerapatan pohon, penentuan titik pengambilan data dilakukan berdasarkan metode purposive. Suhu dan kelembaban udara dikumpulkan dengan cara pengukuran dalam waktu 5 minggu menggunakan alat termohigrometer, sedangkan untuk data persepsi dikumpulkan dengan wawancara menggunakan kuesioner. Hasil dari identifikasi vegetasi pohon menunjukkan adanya pengaruh kerapatan vegetasi terhadap suhu dan kelembaban udara yag mempengaruhi tingkat kenyamanan dengan komposisi jenis vegetasi didominasi oleh jenis Gmelina (Gmelina arborea). Nilai THI di dalam kawasan Hutan Kota Bungkirit dapat dikategorikan nyaman dilihat dari rata-rata pada 5 minggu, indeks kenyamanan mencapai 24,25, sedangkan di luar kawasan masuk ke dalam kategori tidak nyaman dengan rata-rata indeks kenyamanan mencapai 26,73 yang artinya nilai tersebut melebihi tingkat kategori sedang yaitu 26. Tingkat kenyamanan Hutan Kota Bungkirit berdasarkan persepsi tergolong tinggi sebesar 87,5% menyatakan nyaman.